Changing the stability of polymer-based memory devices in high conductivity state via tuning the red-ox property of Hemin. (23rd July 2015) - Zhang, Chun-Yu; He, Jing-Hui; Lu, Cai-Jian; Gu, Qian-Feng; Wu, Lin-Xin; Liu, Quan; Li, Hua; Xu, Qing-Feng; Lu, Jian-Mei
Abstract: Two polymer-Hemin composites, AB type block copolymer (PStCH- b -P4VP): Hemin and homopolymer of poly(4-vinylpyridine) (P4VP): Hemin, can be fabricated into sandwich memory devices. The memory device characteristics of the PStCH- b -P4VP: Hemin blends can show Flash memory behavior, while the P4VP polymer with Hemin only shows write-once-read-many-times (WORM) performance. Charge transfer and nanocomposite redox are probably responsible for the conductance-switching behavior. The results of cyclic voltammogram (CV) measurement indicate that the reversible Fe III /Fe II redox reaction is preserved well in the composite PStCH- b -P4VP: Hemin, while only polymer oxidation is observed in the P4VP: Hemin system. Due to the hindrance of StCH moiety, the coordination of pyridine and Fe II can keep the Fe II active. The P4VP has a more flexible chain that saturates the Fe II center and results in stable coordination; Fe III /Fe II redox reaction is therefore an obstacle. By tuning the coordination surroundings of the metal ion, different memory types can be obtained. Graphical abstract: Highlights: The memory devices of PStCH- b -P4VP: Hemin blends show Flash performance. The P4VP polymer with Hemin shows write-once-read-many-times (WORM) performance. The P4VP results in a stable coordination; Fe III /Fe II redox reaction is hindered. The PStCH block can obstruct the coordination between P4VP block and Hemin. The coordination surrounding of Fe (II) center can affect the memory behaviors.